A&T Ethiopia Maternal Nutrition Baseline Survey 2019: Health Extension Worker - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. In Ethiopia, A&T integrated a package of maternal nutrition interventions into existing antenatal care (ANC) services delivered through government health facilities (counselling on diet quality during pregnancy, distribution and promotion of Iron Folic Acid (IFA) supplementation, weight gain monitoring, counselling on early breastfeeding practices, and systems strengthening through training and supportive supervision) and community platforms (home visits, Pregnant Women Conferences/Mother Support groups, and community gatherings) that align with the latest global evidence. This dataset is part of a survey that was conducted to gather baseline data for the impact evaluation of the interventions. The overall study objective was to determine the feasibility of integrating locally relevant maternal nutrition interventions into existing ANC services and determine the impact on diet quality and utilization of nutrition interventions during pregnancy. Research questions include: 1) What is the program impact on maternal practices: (1) consumption of diversified foods during pregnancy; (2) consumption of IFA supplements during pregnancy; and (3) early breastfeeding practices? 2) Can the coverage and utilization of key maternal nutrition interventions during ANC be improved through system strengthening approaches? 3) What factors influenced the integration and strengthening of maternal nutrition interventions into the government ANC service delivery platform? The evaluation used a two-arm cluster-randomized, non-masked trial design, consisting of two cross-sectional surveys at baseline and endline. The unit of randomization is the health center and associated health posts in the catchment area. The baseline survey was conducted in October-November 2019 by Addis Continental Institute of Public Health (ACIPH), the in-country research collaborator for the survey. The baseline survey included the following: 1) Pregnant women questionnaire, 2) Recently delivered women questionnaire, 3) Health Extension Worker (HEW) questionnaire, 4), Nurse-midwife questionnaire, and 5) Health facility observation checklist. The HEW interviews were conducted using pretested, structured questionnaires. Information was collected on work responsibilities, time commitments and workload, capacity, knowledge, motivation, supervision, and ANC service provision at the health post.